1992
DOI: 10.2307/4002906
|View full text |Cite
|
Sign up to set email alerts
|

Shrub Control and Seeding Influences on Grazing Capacity in Argentina

Abstract: Total vegetation cover, forage species cover, litter cover, and carrying capacity were determined during 3 growing seasons (1979-80,1980-81, and 1981-82), for plots cleared of shrubs with or without sowing of native grasses in a site characteristic of the Monte Phytogeographical Province in mid-west Argentina. We tested the hypothesis that shrub removal with or without sowing of native grasses increases aerial cover of forage, especially species capable of quick establishment ("pioneers"), that ultimately resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…Passera et al (1992) reported shrub cleared and shrub cleared þ native grass sown treatments increased perennial grass cover with respect to control treatment, but did not find significant difference in perennial grass cover between both treatments. However, buffelgrass was not sown in either study.…”
Section: Resultsmentioning
confidence: 66%
“…Passera et al (1992) reported shrub cleared and shrub cleared þ native grass sown treatments increased perennial grass cover with respect to control treatment, but did not find significant difference in perennial grass cover between both treatments. However, buffelgrass was not sown in either study.…”
Section: Resultsmentioning
confidence: 66%
“…In the Central Monte, mechanical shrub control may increase grass cover, resulting in an increase of the carrying capacity of some communities (Passera et al, 1992). This effect is more evident in Larrea cuneifolia communities, with poor grass coverage, than in Larrea divaricata communities, in which grasses are more abundant (Passera et al, 1996).…”
Section: Wood Clearcuting In the Monte Regionmentioning
confidence: 98%
“…In the early stages, it is possible to stop or minimize the process of degradation through management practices by altering the grazing season, stocking density, and animal type (Westoby et al, 1989). In the later stages, however, the activities taken up for controlling the process of degradation are unlikely to be effective, as they would require removal of livestock from the affected area as well as soil and vegetation manipulation (Gibbens et al, 1992;Passera et al, 1992).…”
Section: Consequences Of Overgrazingmentioning
confidence: 99%